Pengaruh Kinerja Keuangan terhadap Harga Saham Perusahaan Sektor Makanan dan Minuman - Roy Budiharjo (Neolectura, 2022)
The purpose of this study was to determine the effect of liquidity, total asset turnover and firm size on stock prices. Secondary data collected by sample from food and beverage sector companies listed on the Indonesian stock exchange for the period 2017 – 2020. Sampling in this study using the purposive sampling method with the criteria as (1) listed on the Indonesia Stock Exchange in 2017 - 2020. (The data needed in this study taken from the Indonesian Capital Market Directory (ICMD) 2017-2020. Statistical tests carried out by t-test and linear regression analysis Before this test, the classical assumption test was carried out.The results of the study showed that firm size had a positive effect on stock prices, while liquidity and total asset turnover had no effect on stock prices.